Peran zakat dalam mengatasi kemiskinan - ramadhan, gilang (Maliki Interdisciplinary Journal, 2025)
Poverty is a complex social and economic problem and continues to cause tension in many countries, including Indonesia. Even though the government has taken several steps to overcome poverty, the results are still not completely satisfactory. In this context, zakat is one of the pillars of Islamic economics, offering a potentially profitable solution. Zakat not only functions as a religious obligation, but also functions as a social tool that can help distribute wealth more fairly, prevent people from stealing it, and provide support to those in need. Zakat is an obligation to pay out a certain portion of one's wealth which must be given to the entitled group at a specified time and amount. Zakat plays an important role in addressing problems such as poverty, both in the short and long term.